2006
DOI: 10.1016/j.virol.2005.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the transmembrane domain of Vpu in simian–human immunodeficiency virus (SHIVKU1bMC33) with that of M2 of influenza A results in a virus that is sensitive to inhibitors of the M2 ion channel and is pathogenic for pig-tailed macaques

Abstract: The Vpu protein of human immunodeficiency virus type 1 has been shown to shunt the CD4 receptor molecule to the proteasome for degradation and to enhance virus release from infected cells. The exact mechanism by which the Vpu protein enhances virus release is currently unknown but some investigators have shown that this function is associated with the transmembrane domain and potential ion channel properties. In this study, we determined if the transmembrane domain of Vpu could be functionally substituted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…None of the mutations were found to disrupt the α-helical region (data not shown). Previously, we showed that fusion of the Vpu protein to enhanced green fluorescent protein (EGFP) still resulted in the ability to down-modulate cell surface CD4 (Hout et al, 2005; 2006; Singh et al, 2003). We analyzed cell surface CD4 expression of the ten Vpu mutant proteins with the unmodified subtype B (VpuEGFP) as a positive control and a Vpu protein with both serine residues of the two casein kinase II sites changed to glycine residues (Vpu S52,56G EGFP) as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…None of the mutations were found to disrupt the α-helical region (data not shown). Previously, we showed that fusion of the Vpu protein to enhanced green fluorescent protein (EGFP) still resulted in the ability to down-modulate cell surface CD4 (Hout et al, 2005; 2006; Singh et al, 2003). We analyzed cell surface CD4 expression of the ten Vpu mutant proteins with the unmodified subtype B (VpuEGFP) as a positive control and a Vpu protein with both serine residues of the two casein kinase II sites changed to glycine residues (Vpu S52,56G EGFP) as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Since scrambling the TM domain blocks both ion channel activity and efficient virus release, it was thought that these activities were related (10,57). Indeed, amiloride-based drugs that block Vpu channel function have been shown to display antiviral activity against HIV-1 in (tetherin-positive) macrophages (9), and other studies report that chimeric Vpu proteins bearing the TM domain of the influenza A virus proton channel M2 were functional for virus release and sensitive to rimantadine (19,20). However, since we found that mutation of S23, known to be required for channel activity (60) and the potential target for amilorides (26), had no effect on tetherin inactivation in our assays, there appears to be a discrepancy in directly correlating cation transport and virus release (tetherin antagonism).…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the M2 TMD histidine residue with an alanine resulted in a constitutively open channel, indicating its importance to channel activation [32, 33, 68, 78]. Using this as a basis, we first made a simian human immunodeficiency virus (SHIV) in which the TMD of Vpu was exchanged with the TMD of M2 [34]. This virus, SHIV M2 , was capable of causing a severe loss of CD4 + T cells and AIDS when inoculated into macaques.…”
Section: Is Vpu An Ion Channel Protein?mentioning
confidence: 99%
“…SIV cpz CAM13, SIV cpz ANT, and SIV cpz TAN1 only contain a single casein kinase II site. All four vpu isolates were fused in frame to the gene for enhanced green fluorescence protein (EGFP) and expressed under the control of a CMV promoter, similar to the HIV-1 subtype B vpu genes our laboratory has previously analyzed [34, 35, 74]. All four SIV cpz Vpu fusion proteins were membrane-associated, partially co-localized with DsRed-ER and ECFP-Golgi marker proteins, and completely co-localized with an ECFP-Membrane marker.…”
Section: The Cd4 Down-modulation Function Is Conserved In Vpu Proteinmentioning
confidence: 99%